BUDAYA DISIPLIN DALAM BERLALU LINTAS KENDARAAN RODA DUA DI KOTA BANDUNG - Sadono, Soni (PKn Progresif, 2017)
This research was conducted as concerns against the traffic of Bandung is increasingly solid ESP. two-wheeled vehicle. It is caused by the increase of vehicles which are not accompanied by a good level of discipline. Two-wheel vehicle ownership from the socio-cultural community is a reflection of social status. The approach used in the study is qualitative method with Phenomenology. Engineering data collection done by observation or field observations, interviews, and documentation. Meanwhile, engineering data analysis done by stages in accordance with the phenomenological method. The findings of the research is two-wheel drive discipline internalization in Bandung can be realized by establishing: (a) the attitude of discipline as a development that comes from practice, mind control and the control of other persons, (b) the planting of a good understanding of the regulatory system for two-wheel drive disciplined behavior, (c) behavioural Attitude or behavior that reasonably indicate the seriousness of heart, to keep everything orderly and carefully.